High-viscosity plastic material and application thereof
Through the technical means of modifying corundum and dopamine-coated mullite combined with calcium sulfate-modified silica sol, the problems of insufficient flexural strength, compressive strength and wear resistance of existing wear-resistant plastic materials are solved, and higher flexural strength, compressive strength and wear resistance are achieved.
Patent Information
- Application Number
- CN202510132247.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The flexural strength of existing wear-resistant plastic materials is not high, the compressive strength is low, and the wear-resistant performance is poor, which seriously affects its actual use.
By using modified corundum with dopamine coated mullite as aggregate and adding calcium sulfate modified silicon sol, the microstructure of the plastic material is optimized, the flexural strength and compressive strength are improved, while ensuring good wear resistance.
It effectively improves the flexural strength and compressive strength of the plastic material, while also improving the wear resistance and improving the overall performance of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory plastic materials, and in particular relates to a high-viscosity plastic material and application thereof. Background Art
[0002] In order to produce ceramic products with a long life, the original composition of the ceramic clay can be optimized to form a thermally stable structure, but the thermal expansion coefficient can be achieved without reducing it. The products made by non-firing technology and using ceramic plastics and phosphate binders have high porosity, relatively low density and high deformation performance. Refractory plastic materials are a kind of amorphous refractory materials that are hard mud paste and maintain high plasticity for a long time, which are composed of granular and powdery materials, plastic clay and other binders and plasticizers, and then a small amount of water is added.
[0003] A Chinese patent (publication number CN116589267A) discloses a wear-resistant plastic material and its preparation method and application. The invention uses alumina-based homogenous material and mullite as aggregates, magnesium oxide and aluminum oxide powder as powders, phosphoric acid and aluminum dihydrogen phosphate as binders, calcium aluminate cement as a hardening agent, and soft clay is added on this basis, and copper fiber is added as a reinforcing material; the prepared wear-resistant plastic material has the advantages of uniform and dense structure, high strength, excellent wear resistance, good volume stability, etc., which can meet the use conditions of the lining of waste heat power generation equipment, and can effectively ensure the safe and stable operation of the equipment, which is of great significance to improving the operating efficiency of the waste heat power generation system, reducing production costs, and saving resources and energy. However, the patent does not solve the problems of low flexural strength, low compressive strength, and poor wear resistance of plastic materials in the prior art, which seriously affects its actual use.
[0004] Therefore, there is an urgent need for a high-viscosity plastic material. By modifying aggregates such as corundum and mullite and introducing functional components, the flexural strength of the plastic material can be improved, the compressive strength can be increased, and good wear resistance can be ensured. Summary of the invention
[0005] The purpose of the present invention is to provide a high-viscosity plastic material and its application, by using modified corundum and dopamine-coated mullite as aggregates, and adding calcium sulfate-modified silica sol, the flexural strength of the plastic material is effectively improved, the compressive strength is increased, and good wear resistance is ensured.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: The first aspect of the present invention provides a high-viscosity plastic material, wherein the plastic material is made of the following components in parts by weight: 35~40 parts of modified corundum, 25~30 parts of mullite, 10~15 parts of phosphate binder, 10~15 parts of silica sol, 2~4 parts of accelerator and 3~6 parts of plasticizer; The preparation method of the modified corundum comprises: adding 4 to 6 parts of diammonium hydrogen phosphate to 80 to 100 parts of deionized water by weight, stirring and dissolving to obtain a diammonium hydrogen phosphate aqueous solution, then adding 20 to 30 parts of corundum and stirring for 2 to 4 hours, adjusting the pH value to 5.4 to 5.8 and stirring for 8 to 10 hours, standing at room temperature for 16 to 20 hours, and drying at 80 to 90° C. to obtain an intermediate; uniformly mixing 200 to 240 parts of the intermediate with 6 to 10 parts of n-butyl mercaptan and stirring for reaction, cooling after the stirring reaction is completed, suction filtering, and drying to obtain the modified corundum.
[0007] As a preferred solution, the particle size of the corundum is 2.4-2.6 μm.
[0008] As a preferred solution, the stirring reaction conditions include: under a hydrogen atmosphere, a pressure of 1-3 MPa, a temperature of 150-160° C., and a time of 2-4 h.
[0009] Modified corundum can optimize the microstructure of plastic materials, reduce porosity and increase density, so that defects such as microcracks inside the material are significantly reduced. Tighter particle bonding not only improves the overall strength of the material, but also enhances its ability to resist external stress, thereby effectively improving the flexural strength of the plastic material.
[0010] As a preferred solution, the silica sol is calcium sulfate modified silica sol; the preparation method of the calcium sulfate modified silica sol comprises: in parts by weight, 50-60 parts of anhydrous ethanol and 10-20 parts of deionized water are mixed evenly, then 40-50 parts of ethyl silicate 40 are added, stirred at 50-60° C. for 2-4 hours, after cooling to room temperature, 2-4 parts of hydrochloric acid are added and stirred for 20-24 hours, then 4-6 parts of calcium sulfate whiskers are added and stirred for 20-30 minutes, and finally 1-3 parts of 3-aminopropyltriethoxysilane are added for amination reaction to obtain calcium sulfate modified silica sol.
[0011] As a preferred solution, the conditions of the amination reaction include: controlling the pH to 7.6-7.8, the temperature to 62-68° C., and the time to 12-14 h.
[0012] The calcium sulfate whiskers in the calcium sulfate-modified silica sol have high strength and can provide mechanical reinforcement on a macro scale. The silica particles in the silica sol can fill tiny pores, fill the voids at the micro level and enhance interfacial bonding. The two work synergistically to increase the compressive strength of the plastic material.
[0013] As a preferred solution, the mullite is dopamine-coated mullite; the preparation method of the dopamine-coated mullite comprises: mixing 100-120 parts of anhydrous ethanol and 100-120 parts of acetone in parts by weight, then adding 20-30 parts of mullite, reflux reacting at 70-80°C for 2-4 hours, filtering, washing with deionized water, and drying to obtain pretreated mullite; mixing 2-4 parts of 6-hydroxydopamine hydrochloride and 200-300 parts of deionized water, adjusting the pH to 8.2-8.6, then adding 30-40 parts of pretreated mullite, stirring at 60-70°C for 20-24 hours, filtering, washing with deionized water, and vacuum drying to obtain dopamine-coated mullite.
[0014] Dopamine-coated mullite can improve the dispersion of mullite particles in the plastic material matrix, prevent particle aggregation, and ensure the uniformity of the internal structure of the material. At the same time, dopamine can form an additional protective layer on the surface of mullite particles, reducing the impact of direct wear on mullite, thereby improving the overall wear resistance of the plastic material.
[0015] As a preferred solution, the phosphate binder is a magnesium phosphate binder and a chromium phosphate binder; the mass ratio of the magnesium phosphate binder to the chromium phosphate binder is (1~2):1.
[0016] The present invention selects magnesium phosphate and chromium phosphate as phosphate binders and controls the mass ratio of the magnesium phosphate and the chromium phosphate to achieve a good compounding effect, thereby forming a mixed structure of an amorphous mosaic gel-like structure and a glass phase. These structures provide a strong cohesive force between the mixture and the hard surface through an extended hydrogen bond network, thereby improving the flexural strength and compressive strength of the plastic material and ensuring good wear resistance.
[0017] As a preferred solution, the coagulant is selected from any one of hexamethylenetetramine, urea, and biuret, or a combination of at least two of them.
[0018] As a preferred solution, the plasticizer is selected from any one of bentonite, kaolin, and sepiolite powder, or a combination of at least two of them.
[0019] A second aspect of the present invention provides an application of the high-viscosity plastic material as described in the first aspect in the field of hanging pipes.
[0020] In order to achieve the above object, the present invention provides the following technical solutions: Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The dopamine-coated mullite of the present invention contains active groups of hydroxyl and amino, which can be combined with the thiol group in the modified corundum through the amino group, and can also react with the amino group introduced by the calcium sulfate-modified silica sol through the hydroxyl group. The network interconnection structure is constructed based on the dopamine-coated mullite, which effectively improves the flexural strength of the plastic material, increases the compressive strength, and obtains good wear resistance.
[0021] 2. The modified corundum of the present invention can optimize the microstructure of plastic materials, reduce porosity and increase density, so that defects such as microcracks inside the material are significantly reduced. Tighter particle bonding not only improves the overall strength of the material, but also enhances its ability to resist external stress, thereby effectively improving the flexural strength of the plastic material.
[0022] 3. The calcium sulfate whiskers in the calcium sulfate-modified silica sol of the present invention have high strength and can provide mechanical reinforcement on a macro scale. The silicon dioxide particles in the silica sol can fill tiny pores, fill the gaps at the micro level and enhance the interface bonding. The two work synergistically to increase the compressive strength of the plastic material.
[0023] 4. The dopamine-coated mullite of the present invention can improve the dispersibility of mullite particles in the plastic material matrix and prevent the aggregation of particles, thereby ensuring the uniformity of the internal structure of the material. At the same time, dopamine can form an additional protective layer on the surface of mullite particles, which can reduce the impact of direct wear on mullite through the protective layer, thereby improving the overall wear resistance of the plastic material. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The sources of some components in the embodiments and comparative examples are as follows: Corundum I, product number CL370, particle size 2.6 μm, purchased from Qingdao Anmai Aluminum Company; Corundum II, product number CT800, particle size 3.4 μm, purchased from Qingdao Anmai Aluminum Company; Corundum III, product number CTC50, particle size 1.7 μm, purchased from Qingdao Anmai Aluminum Co., Ltd. Mullite, model JSM-70, purchased from Jiangsu Jingxin New Materials Co., Ltd.; Magnesium phosphate binder, CAS No. 10233-87-1, purchased from Sinopharm Chemical Reagent Co., Ltd.; Chromic phosphate binder, CAS No. 10101-59-4, purchased from Sinopharm Chemical Reagent Co., Ltd.; Silica sol, product number JR1007b, was purchased from Henan Jinrun New Materials Co., Ltd.; Hexamethylenetetramine, CAS No. 100-97-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Urea, CAS No. 57-13-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Biuret, CAS No. 108-19-0, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Bentonite, CAS No. 1302-78-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Kaolin, CAS No. 1332-58-7, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Sepiolite powder, CAS No. 63800-37-3, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Diammonium hydrogen phosphate, CAS No. 7783-28-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.; n-Butyl mercaptan, CAS No. 109-79-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Ethyl silicate 40, CAS No. 11099-06-2, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; 3-Aminopropyltriethoxysilane, CAS No. 919-30-2, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Calcium sulfate whiskers, brand NP-M02-I30, were purchased from Jiangxi Fengzhu New Material Technology Co., Ltd.; 6-Hydroxydopamine hydrochloride, product number H135753, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0026] Example 1 This embodiment provides a high-viscosity plastic material, which is made of the following components in parts by weight: 40 parts of modified corundum, 25 parts of dopamine-coated mullite, 15 parts of phosphate binder (10 parts of magnesium phosphate binder and 5 parts of chromium phosphate binder), 15 parts of calcium sulfate-modified silica sol, 4 parts of coagulant hexamethylenetetramine and 6 parts of plasticizer bentonite; Preparation of the modified corundum: by weight, 6 parts of diammonium hydrogen phosphate are added to 100 parts of deionized water, stirred and dissolved to obtain a diammonium hydrogen phosphate aqueous solution, and then 30 parts of corundum I (article number CL370, particle size 2.6 μm) are added and stirred for 4 hours, and the pH is adjusted to 5.8 and stirred for 10 hours, and then allowed to stand at room temperature for 20 hours, and dried at 90° C. to obtain an intermediate; 240 parts of the intermediate and 10 parts of n-butyl mercaptan are mixed uniformly and stirred for reaction (under a hydrogen atmosphere, pressure of 3 MPa, temperature of 160° C., time of 2 hours), and after the stirring reaction is completed, the mixture is cooled, filtered, and dried to obtain the modified corundum; Preparation of the calcium sulfate modified silica sol: in parts by weight, 60 parts of anhydrous ethanol and 20 parts of deionized water are mixed evenly, then 50 parts of ethyl silicate 40 are added, stirred at 60° C. for 2 hours, cooled to room temperature, 4 parts of hydrochloric acid are added, stirred for 24 hours, 6 parts of calcium sulfate whiskers are added, and stirred for 30 minutes, and finally 3 parts of 3-aminopropyltriethoxysilane are added for amination reaction (control the pH at 7.8, the temperature at 68° C., and the time at 12 hours) to obtain the calcium sulfate modified silica sol.
[0027] The preparation of the dopamine-coated mullite is as follows: by weight, 120 parts of anhydrous ethanol and 120 parts of acetone are mixed evenly, then 30 parts of mullite are added, the mixture is refluxed at 80° C. for 2 hours, filtered, washed with deionized water, and dried to obtain pretreated mullite; 4 parts of 6-hydroxydopamine hydrochloride and 300 parts of deionized water are mixed evenly, the pH is adjusted to 8.6, 40 parts of the pretreated mullite are added, the mixture is stirred at 70° C. for 20 hours, filtered, washed with deionized water, and dried in vacuo to obtain dopamine-coated mullite.
[0028] Example 2 This embodiment provides a high-viscosity plastic material, which is made of the following components in parts by weight: 35 parts of modified corundum, 25 parts of dopamine-coated mullite, 10 parts of phosphate binder (5 parts of magnesium phosphate binder and 5 parts of chromium phosphate binder), 10 parts of calcium sulfate-modified silica sol, 2 parts of urea as a coagulant and 3-6 parts of kaolin as a plasticizer; Preparation of the modified corundum: by weight, 4 parts of diammonium hydrogen phosphate are added to 80 parts of deionized water and stirred to dissolve to obtain a diammonium hydrogen phosphate aqueous solution, then 20 parts of corundum I (article number CL370, particle size 2.6 μm) are added and stirred for 2 hours, the pH is adjusted to 5.4 and then stirred for 8 hours, and then allowed to stand at room temperature for 16 hours, and dried at 80° C. to obtain an intermediate; 200 parts of the intermediate and 6 parts of n-butyl mercaptan are mixed evenly and stirred to react (under a hydrogen atmosphere, a pressure of 1 MPa, a temperature of 150° C., and a time of 4 hours), and after the stirring reaction is completed, the mixture is cooled, filtered, and dried to obtain the modified corundum; Preparation of the calcium sulfate modified silica sol: in parts by weight, 50 parts of anhydrous ethanol and 10 parts of deionized water are mixed evenly, then 40 parts of ethyl silicate 40 are added, stirred at 50° C. for 2 hours, cooled to room temperature, 2 parts of hydrochloric acid are added and stirred for 20 hours, then 4 parts of calcium sulfate whiskers are added and stirred for 20 minutes, and finally 1 part of 3-aminopropyltriethoxysilane is added for amination reaction (control the pH at 7.6, the temperature at 62° C., and the time at 14 hours) to obtain the calcium sulfate modified silica sol.
[0029] The preparation of the dopamine-coated mullite is as follows: by weight, 100 parts of anhydrous ethanol and 100 parts of acetone are mixed evenly, then 20 parts of mullite are added, the mixture is refluxed at 70° C. for 4 hours, filtered, washed with deionized water, and dried to obtain pretreated mullite; 2 parts of 6-hydroxydopamine hydrochloride and 200 parts of deionized water are mixed evenly, the pH is adjusted to 8.2, 30 parts of the pretreated mullite are added, the mixture is stirred at 60° C. for 24 hours, filtered, washed with deionized water, and dried in vacuo to obtain dopamine-coated mullite.
[0030] Example 3 This embodiment provides a high-viscosity plastic material, which is made of the following components in parts by weight: 38 parts of modified corundum, 28 parts of dopamine-coated mullite, 12 parts of phosphate binder (7 parts of magnesium phosphate binder and 5 parts of chromium phosphate binder), 12 parts of calcium sulfate modified silica sol, 3 parts of coagulant biuret and 3-6 parts of plasticizer sepiolite powder; Preparation of the modified corundum: by weight, 5 parts of diammonium hydrogen phosphate are added to 90 parts of deionized water and stirred to dissolve to obtain a diammonium hydrogen phosphate aqueous solution, then 25 parts of corundum I (article number CL370, particle size 2.6 μm) are added and stirred for 3 hours, the pH is adjusted to 5.6 and stirred for 9 hours, and the mixture is allowed to stand at room temperature for 18 hours, and dried at 85° C. to obtain an intermediate; 220 parts of the intermediate and 8 parts of n-butyl mercaptan are mixed evenly and stirred to react (under a hydrogen atmosphere, pressure of 2 MPa, temperature of 155° C., and time of 3 hours), and after the stirring reaction is completed, the mixture is cooled, filtered, and dried to obtain the modified corundum; Preparation of the calcium sulfate modified silica sol: in parts by weight, 55 parts of anhydrous ethanol and 15 parts of deionized water are mixed evenly, then 45 parts of ethyl silicate 40 are added, stirred at 55° C. for 3 hours, cooled to room temperature, 3 parts of hydrochloric acid are added and stirred for 22 hours, then 5 parts of calcium sulfate whiskers are added and stirred for 25 minutes, and finally 2 parts of 3-aminopropyltriethoxysilane are added for amination reaction (control the pH at 7.7, the temperature at 65° C., and the time at 13 hours) to obtain the calcium sulfate modified silica sol.
[0031] The preparation of the dopamine-coated mullite is as follows: by weight, 110 parts of anhydrous ethanol and 110 parts of acetone are mixed evenly, then 25 parts of mullite are added, refluxed and reacted at 75° C. for 3 hours, filtered, washed with deionized water, and dried to obtain pretreated mullite; 3 parts of 6-hydroxydopamine hydrochloride and 250 parts of deionized water are mixed evenly, the pH is adjusted to 8.4, and then 35 parts of the pretreated mullite are added, stirred at 65° C. for 22 hours, filtered, washed with deionized water, and vacuum dried to obtain dopamine-coated mullite.
[0032] Comparative Example 1 The difference between this comparative example and Example 1 is that corundum I is used instead of modified corundum, and the rest is the same as Example 1.
[0033] Comparative Example 2 The difference between this comparative example and Example 1 is that corundum II is used instead of corundum I to prepare the modified corundum, and the rest is the same as Example 1.
[0034] Comparative Example 3 The difference between this comparative example and Example 1 is that corundum III is used to replace corundum I to prepare the modified corundum, and the rest is the same as Example 1.
[0035] Comparative Example 4 The difference between this comparative example and Example 1 is that commercially available silica sol (article number JR1007b) is used to replace the calcium sulfate-modified silica sol, and the rest is the same as Example 1.
[0036] Comparative Example 5 The difference between this comparative example and Example 1 is that commercially available mullite (model JSM-70) is used instead of dopamine-coated mullite, and the rest is the same as Example 1.
[0037] Comparative Example 6 The difference between this comparative example and Example 1 is that the amount of magnesium phosphate binder in the phosphate binder is changed to 12 parts, the amount of chromium phosphate binder is changed to 3 parts, and the others are the same as Example 1.
[0038] Comparative Example 7 The difference between this comparative example and Example 1 is that the amount of magnesium phosphate binder in the phosphate binder is changed to 5 parts, the amount of chromium phosphate binder is changed to 10 parts, and the rest is the same as Example 1.
[0039] Performance Testing The plastic materials of the above embodiments and comparative examples were subjected to the following tests: (1) Flexural strength test The flexural strength is tested according to the requirements of GB / T 4513.6-2017 Unshaped refractory materials Part 6: Determination of physical properties.
[0040] (2) Compressive strength test The compressive strength is tested according to the requirements of GB / T 4513.6-2017 Unshaped refractory materials Part 6: Determination of physical properties.
[0041] (3) Wear resistance test The wear resistance is tested according to the requirements of GB / T 18301-2012 Test method for wear resistance of refractory materials at room temperature.
[0042] Table 1 Performance test results
[0043] It can be seen from the above performance test results that the plastic material of Examples 1-3 has the best comprehensive performance, with a flexural strength of 28.8~29.5MPa, a compressive strength of 97.4~98.2MPa, and a wear resistance of 8.14~8.35cm³; this is mainly because it uses modified corundum and dopamine-coated mullite as aggregates, and adds calcium sulfate-modified silica sol, which effectively improves the flexural strength of the plastic material, increases the compressive strength, and ensures good wear resistance.
[0044] The comparative example did not adopt the necessary technical solution, resulting in that it was significantly worse than the embodiment in the corresponding performance test; compared with Example 1, the comparative example 1 used corundum I instead of modified corundum, and the flexural strength was reduced, the compressive strength was reduced, and the wear resistance value was increased; compared with Example 1, the comparative example 2 used corundum II instead of corundum I to prepare the modified corundum, and because the particle size of corundum II was too large and the modification effect was not good, the flexural strength was reduced, the compressive strength was reduced, and the wear resistance value was increased; compared with Example 1, the comparative example 3 used corundum III instead of corundum I to prepare the modified corundum, and because the particle size of corundum III was too small and the modification effect was not good, the flexural strength was reduced, the compressive strength was reduced, and the wear resistance value was increased; compared with Example 1, the comparative example 4 used commercially available silica sol (article number JR1007b) instead of calcium sulfate modified silica sol, and the flexural strength was reduced, the compressive strength was reduced, and the wear resistance value was increased. The flexural strength is reduced, and the wear resistance value is increased; compared with Example 1, in Comparative Example 5, commercially available mullite (model JSM-70) is used instead of dopamine-coated mullite, and the flexural strength is reduced, the compressive strength is reduced, and the wear resistance value is increased; compared with Example 1, the amount of magnesium phosphate binder in the phosphate binder of Comparative Example 6 is changed to 12 parts, and the amount of chromium phosphate binder is changed to 3 parts. The amount of magnesium phosphate binder is too much, and the compounding effect is not good, then the flexural strength is reduced, the compressive strength is reduced, and the wear resistance value is increased; compared with Example 1, the amount of magnesium phosphate binder in the phosphate binder of Comparative Example 7 is changed to 5 parts, and the amount of chromium phosphate binder is changed to 10 parts. The amount of magnesium phosphate binder is too little, and the compounding effect is not good, then the flexural strength is reduced, the compressive strength is reduced, and the wear resistance value is increased; the above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.
Claims
1. A high-viscosity plastic material, characterized in that: The plastic material is made of the following components in parts by weight: 35~40 parts of modified corundum, 25~30 parts of mullite, 10~15 parts of phosphate binder, 10~15 parts of silica sol, 2~4 parts of accelerator and 3~6 parts of plasticizer; The preparation method of the modified corundum comprises: adding 4 to 6 parts of diammonium hydrogen phosphate to 80 to 100 parts of deionized water by weight, stirring and dissolving to obtain a diammonium hydrogen phosphate aqueous solution, then adding 20 to 30 parts of corundum and stirring for 2 to 4 hours, adjusting the pH value to 5.4 to 5.8 and stirring for 8 to 10 hours, standing at room temperature for 16 to 20 hours, and drying at 80 to 90° C. to obtain an intermediate; uniformly mixing 200 to 240 parts of the intermediate with 6 to 10 parts of n-butyl mercaptan and stirring for reaction, cooling after the stirring reaction is completed, suction filtering, and drying to obtain the modified corundum.
2. A high-viscosity plastic material according to claim 1, characterized in that: The particle size of the corundum is 2.4-2.6 μm.
3. A high-viscosity plastic material according to claim 1, characterized in that: The stirring reaction conditions include: under hydrogen atmosphere, pressure of 1-3 MPa, temperature of 150-160° C., and time of 2-4 h.
4. A high-viscosity plastic material according to claim 1, characterized in that: The silica sol is calcium sulfate modified silica sol; The preparation method of the calcium sulfate modified silica sol comprises: mixing 50-60 parts of anhydrous ethanol and 10-20 parts of deionized water in parts by weight, then adding 40-50 parts of ethyl silicate 40, stirring at 50-60° C. for 2-4 hours, cooling to room temperature, adding 2-4 parts of hydrochloric acid and stirring for 20-24 hours, then adding 4-6 parts of calcium sulfate whiskers and stirring for 20-30 minutes, and finally adding 1-3 parts of 3-aminopropyltriethoxysilane for amination reaction to obtain the calcium sulfate modified silica sol.
5. A high-viscosity plastic material according to claim 4, characterized in that: The conditions of the amination reaction include: controlling the pH to be 7.6-7.8, the temperature to be 62-68° C., and the time to be 12-14 h.
6. A high-viscosity plastic material according to claim 1, characterized in that: The mullite is dopamine-coated mullite; The preparation method of dopamine-coated mullite comprises: mixing 100-120 parts of anhydrous ethanol and 100-120 parts of acetone by weight, then adding 20-30 parts of mullite, performing reflux reaction at 70-80°C for 2-4 hours, filtering, washing with deionized water, and drying to obtain pretreated mullite; and mixing 2-4 parts of 6-hydroxydopamine hydrochloride and 200-300 parts of deionized water, adjusting the pH to 8.2-8.6, adding 30-40 parts of pretreated mullite, stirring at 60-70°C for 20-24 hours, filtering, washing with deionized water, and vacuum drying to obtain dopamine-coated mullite.
7. A high-viscosity plastic material according to claim 1, characterized in that: The phosphate binder is a magnesium phosphate binder and a chromium phosphate binder; the mass ratio of the magnesium phosphate binder to the chromium phosphate binder is (1~2):
1.
8. A high-viscosity plastic material according to claim 1, characterized in that: The coagulant is selected from any one of hexamethylenetetramine, urea and biuret or a combination of at least two thereof.
9. A high-viscosity plastic material according to claim 1, characterized in that: The plasticizer is selected from any one of bentonite, kaolin, and sepiolite powder, or a combination of at least two of them.
10. Use of the high-viscosity plastic material according to any one of claims 1 to 9 in the field of hanging pipes.
Citation Information
Patent Citations
Wear-resistant plastic refractory as well as preparation method and application thereof
CN116589267A